Meta-modeling constructs for requirements reuse (RR): software requirements patterns, variability and traceability / Badamasi Imam Ya'u, Azlin Nordin and Norsaremah Salleh - Ya'u, Badamasi Imam; Nordin, Azlin; Salleh, Norsaremah (Universiti Teknologi MARA Press (Penerbit UiTM), 2018)
Reuse is a fundamental activity, which increases quality and productivity of software products. Reuse of software artifacts, such as requirements, architectures, and codes can be employed at any developmental stage of software. However, reuse at a higher level of abstraction, for instance at requirements level, provides greater benefits in software development than when applied at lower level of abstraction for example at coding level. To achieve full benefits of reuse, a systematic approach and appropriate strategy need to be followed. Although several reuse approaches are reported in the literature, these approaches lack a key strategy to synergize some essential drivers of reuse, which include reusable structure, variability management (VM) and traceability of software artifacts. In line with this, we make our contribution in this paper by (1) presenting the concepts and importance of software requirements patterns (SRP) for reusable structure; (2) proposing a strategy, which combines three sub-disciplines of Software Engineering (SE) such as Requirements Engineering (RE), Software Product Line Engineering (SPLE) and Model-driven Engineering (MDE); (3) proposing a meta-modeling constructs, which include SRP, VM and traceability and; (4) Relationship amongst the three sub-disciplines of the SE. This is a novel approach and we believe it can support and guide researchers and practitioners in SE community to have greater benefits of reuse during software developments.